Accuracy of non-ultrasound guided thyroid gland fine needle aspiration with biopsy - Keshav Grover; James P Dworkin- Valenti; Winston Jadusingh; Samba SR Bathula (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Objectives: The aim of this study was to examine the accuracy of fine needle aspiration with cytology (FNAC) for thyroid gland masses without (US) ultrasound guidance by comparing results with final Histopathological Examination (HPE) findings. Study Design: Retrospective chart review Setting: Tertiary Care Medical Center in Montego Bay, Jamaica. Subjects and Methods: Patient charts were retrospectively reviewed at Cornwall Regional Hospital in Montego Bay, Jamaica. Individuals with thyroid nodules less than 3 cm were excluded. Non-ultrasound guided FNA was performed by the attending otolaryngologist and cytology was analyzed by the attending pathologist. FNAC results were compared to final HPE results. A total of 412 patients were sampled.  Results: The rate of agreement between the results of FNAC and HPE was very high (90%), especially for all benign lesions. Multi-nodular goiter was the most common presentation. Conclusion: Head and neck disease is difficult to identify in developing nations. Results of non-US guided FNAC for thyroid lesions 3 cm and larger proved to be accurate 90% of the time when compared to final HPE results. These data demonstrate the relative reliability of FNAC without US guidance for the vast majority of thyroid gland masses that were evaluated. The findings also support the active role of the otolaryngologist in the diagnostic process; participation that can be efficiently accomplished in a routine ENT out-patient clinic setting.